2008
DOI: 10.1103/physrevb.78.224111
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the structure of the stable and metastable(GeTe)m(Sb2Te

Abstract: Using first-principles calculations, we identify the mechanisms that lead to the lowest energy structures for the stable and metastable ͑GeTe͒ m ͑Sb 2 Te 3 ͒ n ͑GST͒ compounds, namely, strain energy release by the formation of superlattice structures along of the hexagonal ͓0001͔ direction and by maximizing the number of Te atoms surrounded by three Ge and three Sb atoms ͑3Ge-Te-3Sb rule͒ and Peierls-type bond dimerization. The intrinsic vacancies form ordered planes perpendicular to the stacking direction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
143
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(152 citation statements)
references
References 52 publications
9
143
0
Order By: Relevance
“…Despite the seeming simplicity, the structural details of the m-GST structure are still under intense debate. Firstprinciples calculations have found that the intrinsic vacancies form ordered ͑111͒ planes, 32,40 which confirm previous experimental studies based on HRTEM. 38 However, there is also strong evidence for a random distribution of the intrinsic vacancies at high energy configurations, 34 which might depend on the cooling rate from amorphous to crystalline.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…Despite the seeming simplicity, the structural details of the m-GST structure are still under intense debate. Firstprinciples calculations have found that the intrinsic vacancies form ordered ͑111͒ planes, 32,40 which confirm previous experimental studies based on HRTEM. 38 However, there is also strong evidence for a random distribution of the intrinsic vacancies at high energy configurations, 34 which might depend on the cooling rate from amorphous to crystalline.…”
Section: Introductionsupporting
confidence: 71%
“…The GST compound, as well as other compositions, crystallizes in two well known phases, namely, the stable hexagonal [23][24][25][26][27][28][29][30][31] ͑s-GST͒ and metastable rocksalt ͑RS͒ ͑m-GST͒ phases. Experimental studies indicate that only the m-GST phase takes part in optical storage applications; 3,5,[10][11][12][13][14] however, both structures have very similar structure features as discussed by Da Silva et al 32 employing first-principles calculations. The intrinsic vacancies, which originate from Sb 2 Te 3 , are present in both phases; however, the intrinsic vacancies occupy specific lattice sites only in the RS m-GST structure, while it only separate the building GST blocks in the s-GST phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 2 3 , respectively͔͒ suggest that the stability of these compounds is enhanced by maximizing the number of Te atoms surrounded by three Ge and three Sb atoms. 7 The amorphous structures of chalcogenide alloys remain a challenging problem for experimentalists and theorists. Scattering methods provide much less structural information than in crystals with long-range order, although extended x-ray absorption fine structure ͑EXAFS͒ provides details of the local coordination and bond lengths.…”
Section: Introductionmentioning
confidence: 99%
“…They also have many different properties, even different chemical trends. For example, the ground states of free-standing isovalent alloys are generally phase separated, due to the positive mixing enthalpy, but those of the nonisovalent alloys are the ordered alloy structures satisfying the octahedral rule 14,15 . Their electronic structures can also be very different.…”
mentioning
confidence: 99%